Stable isotopic analysis of water utilization characteristics of four xerophytic shrubs in the Hobq Desert, Northern China - Yongsheng, Wu; Zilong, Liao; Xiangqian, Yu; Qiang, Yin; Hui, Wang; Li, Gao (Frontiers in Plant Science, 2023)
Quantitative identification of water utilization characteristics of xerophytic shrubs is an important prerequisite for the selection and optimization of a regional artificial sand-fixing vegetation system. In this study, a hydrogen (δD) stable isotope technique was used to study the changes in water use characteristics of four typical xerophytic shrubs, Caragana korshinskii (C), Salix psammophila (S), Artemisia ordosica (A), and Sabina vulgaris (V) in the Hobq Desert after light (4.8 mm) and heavy (22.4 mm) rainfall events within 1 and 5 days (8 days for heavy rainfall). The results showed that the replenishment of soil water by light rainfall events was very limited, while the replenishment depth of soil water by heavy rainfall reached 60 cm. Under light rainfall, sand-fixing plants C and S primarily used the 80–140 cm layer of soil water (37–70%) and groundwater (13–29%), and the water use characteristics did not change significantly after the light rainfall event. However, the utilization ratio of sand-fixing plant A to soil water in the 0–40 cm layer increased from less than 10% on the first day after rain to more than 97% on the fifth day after rain, whereas the utilization ratio of sand-fixing plant V to soil water in the 0–40 cm layer also increased from 43% to nearly 60%. Under heavy rainfall, the sand-fixing plants C and S still used the 60–140 cm layer (56–99%) and groundwater (~15%), while the main water utilization depth of sand-fixing plants A and V expanded to 0–100 cm. Based on the above results, sand-fixing plants C and S primarily use the soil moisture of the 80–140 cm layer and groundwater, while A and S use the soil moisture of the 0–100 cm layer. Therefore, the co-existence of sand-fixing plants A and V will increase the competition between artificial sand-fixing plants, while the combination of the two plants with C and S will avoid competition between artificial sand-fixing plants to some extent. This study provides important guidance for regional vegetation construction and sustainable management of an artificial vegetation system.